PR Kumaraswamy, Squaring the Circle: Mahatma Gandhi and the Jewish National Home (Historia, 2021)
What was Mahatma Gandhi’s understanding of, and attitude toward, the Jews, Jewish nationalism and the project to establish a Jewish homeland in Palestine? Mainstream history books tell us that though sympathetic towards the Jews, Gandhi opposed theZionist idea of establishing a Jewish national home in Palestine. This he found to be morally unacceptable. Indeed, one of the most widely quoted statements of Gandhi on Palestine emanating from 1938 was that, “.... Palestine belongs to the Arabs in the same sense that England belongs to the English and France to the French...” (p 207). In this well-researched and erudite book, however, PR Kumaraswamy, takes on this conventional wisdom. He points out that Gandhi’s positions regarding the Jews,Jewish nationalism and Israel have been more complex than commonly understood. There were shifts and changes, subtle differences, dualities, and above all, inconsistencies in Gandhi’s position with regards to a Jewish homeland in Palestine. For instance, after his 1938 statement he also admitted that Jews have “a good case”, “a prior claim” to Palestine, and was prepared to admit “the natural desire of the Jews to find a home in Palestine”.
Keywords: Mahatma Gandhi; Palestine; Zionist; PR Kumaraswamy; Hindu-Muslim; British colonialism; India